Measures of performance by means of objective tests versus experimental practices: the opinions of the students (Research, Society and Development, 2019)
The use of only one data collection instrument, such as traditional objective evidence, can be disastrous from the point of view of learning assessment, which is not always effective in assessing what the learner has learned; however, several instruments may be used for this purpose. Thus, a research was carried out seeking to answer the following question:Is it in the students' opinion, only the test tests, sufficient to evaluate their learning?Therefore, the present article is the result of this qualitative research that was carried out with a class of a technical course in chemistry with the purpose of verifying the students' opinions on the methods of evaluation of the discipline, being then questioned about their preferences regarding the application of test tests or experiments performed at home. The result showed almost unanimously that they prefer the low complexity experiments that they frequently do at home during the semester on teacher orientation and mediation. In addition to the questionnaire applied to the 29 students studied, a brief bibliographic review was carried out on the evaluation processes to substantiate and corroborate with the study.